Little Bear's Big Adventure - Hubery, Julia; Guile, Gill. (Melville, New York : Imagine That Group Ltd, 2018)
'Far, far away, in the African Savannah lived a little giraffe called Gregory who had no one to play with'. Join Gregory the little giraffe in the is funny story about friendship and accepting others.
Augmented Reality Book.
Read & Learn As Characters Come Alive! 3D
For ages 1-5 years.
Keywords: Readers -- Juvenile fiction; Basic English; Children's stories; Bear's Juvenile fiction